From Sharh to Caption: Hadith in the New Media - Saifuddin Zuhri Qudsy (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
This article examines the transformation of methods used in commenting on hadith in the era of new media. It addresses three main questions: First, what forms does hadith commentary take in the new media era? Second, what factors have contributed to these changes in the practice of hadith commentary? Third, how has the shift in interpretive meaning occurred as a result of these evolving modes of commentary within the new media environment? The analysis is conducted using an interpretative approach. By employing these methodological steps, the study identifies emerging patterns of hadith commentary in the new media era that differ from earlier models, both in terms of presentation and analytical engagement with hadith material. This study finds, first, that the presentation of hadith commentary on Instagram reflects a significant transformation: what was once primarily text-based is now conveyed through diverse visual formats. These include captions, images, microblogs, and videos, which have revitalized a tradition of commentary that had long been stagnant and underdeveloped. Second, these changes in hadith commentary represent a scholarly response to the rapid evolution of new media technologies, including social media. Third, media technology has enabled hadith commentary—previously confined largely to printed formats—to appear across various online platforms. These accounts may be managed by institutions dedicated to hadith studies or by anonymous individuals, whether operating personally or in other capacities.